Tabela Brasileira de Composição de Alimentos TBCA-USP (Versões 3 e 4) no contexto internacional. - Giuntini, Eliana Bistriche; Lajolo, Franco M.; De Menezes, Elizabete Wenzel (Archivos Latinoamericanos de Nutrición)
The Brazilian Food Composition Table (TBCA-USP) aims to divulge information about Brazilian food composition. Therefore, it adopts international patterns that define rules and criteria for the food composition area, through guides and manuals with protocols to be used for data generation and compilation, which amplifies the communication and exchange between laboratories. From 2001 to 2004, 863 new data were introduced in the TBCA-USP, in a total of 1838 data, 1200 of which refers to proximal composition. During this period, the versions 3.0, 4.0 and 4.1 of the TBCA-USP were developed and put on the Internet. These versions had several structural modifications in relation to the ones before. The version 3.0 of the TBCA-USP used to be separated by groups of foods, due to its large number of information. Once this number kept growing, the versions 4.0/4.1 turned to have their food data showed individually, accessed through the name of the food (in Portuguese, English or scientific name). All data is presented as 100g/food and domestic measurement. There is a form available for compilation of food composition data, in order to stimulate researchers to send and publish data that may be evaluated correctly. The TBCA-USP is being structured similarly to the other international tables that follow patterns of INFOODS (International Network of Food Data Systems); and it is making an effort to create specific databases of nutrients or foods that have functional properties.